POLA RUANG PERMUKIMAN DAN ARSITEKTUR TRADISIONAL KAMPUNG ADAT DUARATO - Nyoman Rema; A.A. Gde Bagus (Forum Arkeologi, 2020)
Duarato Traditional Village is one of the traditional villages in Belu Regency, East Nusa Tenggara, which has space pattern and traditional architecture that still preserved today and reflect the concept of life. This study aims to determine the settlement pattern and architecture of Duarato traditional houses. Data were collected through literature study, direct observation, and interview with traditional figures. The data analyzed qualitatively, then a conclusion is drawn. This study resulted in the unique pattern of the village settlements and the architecture of traditional houses have become the characteristic of Duarato Traditional Village. Based on the analysis, Duarato settlement belongs to cluster pattern. The most sacred area for ancestor worship is built on the highest land and/or the direction of sunrise. The center of activity is in K’sadan, which is surrounded by houses and bosok. The traditional house is in the form of wooden stage house. The space pattern of the house is divided vertically and horizontally which functioned for profane or sacred activities. It is meaningful as an effort to maintain the constancy of tribe personalities. Kampung Adat Duarato merupakan salah satu kampung adat di Kabupaten Belu, Nusa Tenggara Timur, yang memiliki pola ruang dan arsitektur traditional yang masih lestari dan mencerminkan konsep kehidupan masyarakatnya. Penelitian ini bertujuan untuk mengetahui pola ruang permukiman dan arsitektur rumah adat Duarato. Data penelitian ini dikumpulkan melalui studi pustaka, observasi langsung, dan wawancara kepada tokoh adat. Setelah data terkumpul kemudian dianalisis secara kualitatif, dilanjutkan dengan penyimpulan. Penelitian ini menghasilkan temuan bahwa pola ruang permukiman kampung dan arsitektur tradisional rumah adat cukup unik yang menjadi ciri khas Kampung Adat Duarato. Berdasarkan dari hasil analisis, Kampung Adat Duarato menganut pola cluster atau mengelompok. Areal paling suci untuk pemujaan leluhur dibangun pada lahan yang paling tinggi dan/atau arah matahari terbit. Pusat kegiatan berada pada k’sadan, yang dikelilingi oleh rumah dan bosok. Rumah adat kampung ini secara arsitektur berupa rumah panggung dengan konstruksi kayu. Pola ruang rumah ini terbagi secara vertikal dan horizontal yang difungsikan untuk kegiatan yang bersifat profan maupun sakral, yang bermakna sebagai upaya menjaga keajegan kepribadian suku.